Anterior Fontanelle Wormian Bone With Exomphalos Major and Dysmorphic Facial Features: A Previously Unseen Association?. Issue 7 (October 2016) - Reid, Thomas H.; Tam, Amy; Antoniou, Georgia; Ong, Juling
Abstract : Abstract: Wormian bones are independent ossification centers found within cranial sutures or fontanelles. Though common in adult populations, their presence in children can be associated with several conditions such as osteogenesis imperfecta, hypothyroidism, pyknodysostosis, cleidocranial dysostosis, rickets, and acrocallosal syndrome. These conditions encompass a large range of clinical features but there has only been 1 other reported patient of exomphalos occurring concurrently with these ossicles. The authors present the case of a child with an anterior fontanellar Wormian bone, dysmorphic facial features, and exomphalos major born to unaffected parents. The pattern of features seen in this child did not closely match any condition commonly associated with Wormian bones. The only other reported case of both Wormian bone and exomphalos was in a child with acrocallosal syndrome who presented with more severe dysmorphic features than seen here. It is possible that this patient represents a previously unknown association between acrocallosal syndrome and exomphalos or a less severe variant of the condition. Conversely, this patient may possibly illustrate a newly discovered association between Wormian bones, facial dysmorphism, and midline abdominal defects.